Product Quality and Promotion: Key Factors in Clothing Purchasing Decisions in Bandung - Cendikia, Ranny Maulani; Juhana, Dudung; Titi, Titi (P3M, STIE Pasundan, Bandung, Indonesia., 2025)
This research is driven by the challenges faced by a clothing company in Bandung, specifically inadequate product quality and ineffective promotional techniques, which directly affect diminishing consumer purchase decisions. This study seeks to thoroughly analyse the impact of product quality and advertising on consumer purchasing decisions. The primary objective of the study is to evaluate how product quality and promotional strategies might stimulate heightened consumer interest and drive purchasing behaviour. The research approach involved distributing questionnaires to 100 respondents who had made purchases at the company. The gathered data were analyzed with SPSS software version 16 to depict the relationship between variables accurately. The findings suggest that product quality has a significant influence on purchasing decisions, both directly and indirectly through promotions. Promotions have a significant influence, however, less substantial than product quality. These two characteristics greatly influence customer purchase decisions. The findings demonstrate that customers in Bandung exhibit significant concern for the quality of available items and respond favourably to appealing and pertinent advertisements. Consequently, the organisation is recommended to prioritise enhancing product quality and devising innovative, coherent, and focused promotional techniques. The corporation is expected to enhance its market position, increase consumer loyalty, and drive sustainable sales growth through these initiatives. The study concludes that quality and promotion are critical factors influencing consumer purchasing decisions; thus, both must be managed in an integrated and sustainable manner to attain a competitive advantage in the intensifying competition within the Bandung clothing industry.